Geometry Tutoring Supported by an Intelligent Drawing Interface and Automatic Problem Solving - Hyung Joon Kook (International Journal of Computational Intelligence Systems, 2010)
In a scientific domain, learning comprises studying a finite set of principles of the domain and applying them to solve a wide variety of problems. Therefore an intelligent tutoring system in a scientific domain is required to possess an adequate methodology to deal with this principle. We suggest a tutoring architecture for geometry where the domain principles are automatically converted to inference operators for use by the domain-independent, inferential portion of the tutoring system. An important part of this architecture is an intelligent drawing interface that facilitates automatic conversion of the figures in geometry into an internal form that is suitable for problemsolving tutoring. During student problem solving, the system monitors the student’s steps, tracks a step that has multiple inferences, and gives hints and explanations. We discuss the advantages of our approach in enhancing the performance and interactivity of the tutoring system.